Ludwig Pfeiffer's "Culture and the Humanities: Symptomatologies, Mostly Historical, Mainly German": Roundtable Discussion - Adams, Hazard; Behler, Ernst; Birus, Hendrik; Derrida, Jacques; Iser, Wolfgang; Krieger, Murray; Miller, Hillis; Pfeiffer, Ludwig; Readings, Bill; Wang, Ching-hsien; Yu, Pauline (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1996)
This roundtable discussion of "Culture and the Humanities: Symptomatologies, Mostly Historical, Mainly German", Ludwig Pfeiffer's contribution to the first International Conference for Humanistic Discourses, was held in April, 1994. The papers of this first meeting of the ICHD have been published in volume 4 of Surfaces (1994).